Struktur Komunitas Moluska Bentik di Perairan Sekitar PLTU Grati, Pasuruan, Jawa Timur - Arbi, Ucu Yanu (Universitas Atma Jaya Yogyakarta, 2010)
Observation on marine benthic molluscs around PLTU Grati waters in Pasuruan was conducted on May and December 2004. The aim of this study was to determine condition and community structure of benthic molluscs living in those areas. Samples were collected using Eckmann grab and sieved through 0.5 mm mesh-sized. The number of molluscs species is 28 species, consisting of 16 species class of gastropoda and 12 species class of pelecypoda. A diversity index (H) ranged 0.845 to 1.158, an evenness index (J) was 0.856 to 1 and a richness index (D) was 19.562 to 31.949. Littorina undulata (Littorinidae) was a dominant species and was relatively widely distributed. In general, this result showed that around PLTU Grati waters had a relatively low benthic molluscs diversity.